Annuity market imperfection, retirement and economic growth - Ben J. Heijdra; Jochen O. Mierau (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study the effects of an annuity market imperfection on individual agents' labour supply and retirement decisions and on the macroeconomic growth rate in an overlapping generations model with endogenous growth. We model imperfect annuities by introducing a load factor on the interest rate faced by finitely-lived agents. Our core model features age-independent wages and a constant mortality rate. In the first extension we study the implications for microeconomic decisions and macroeconomic outcomes of a hump-shaped life-cycle profile in labour productivity, whilst in the second extension we postulate a realistic mortality process. Our main findings are that the limited availability of annuities induces agents to retire early in the first two models, but later in the model with age-dependent mortality. In all cases, the general equilibrium repercussion is that economic growth is lower under imperfect annuities than with perfect annuities.
Keywords: D52; D91; E10; J20; 330; annuity markets; retirement; endogenous growth; overlapping generations; demography; Private Rentenversicherung; Unvollkommener Markt; Altersgrenze; Arbeitsangebot; Neue Wachstumstheorie; Overlapping Generations; Arbeitsproduktivität; Bevölkerungsökonomie; Theorie